Simplify: `(12x^5)/(3x^5/3)^3`

### 2 Answers | Add Yours

The expression `(12x^5)/(3x^5/3)^3` has to be simplified.

`(12x^5)/(3x^5/3)^3`

= `(12x^5*3^3)/(3x^5)^3`

= `(12x^5*3^3)/(3^3*x^15)`

= `(12x^5)/(x^15)`

= `12/x^10`

**The expression **`(12x^5)/(3x^5/3)^3 = 12/x^10`

If problem is:

`(12x^5)/(3x^5/3)^3` `=(12x^5)/(x^5)^3=(12x^5)/x^15=12x^(5-15)=` `12x^-10=12/x^10`

Instead if problem is:

`(12x^5)/(3x^(5/3))^3` `=(12x^5)/(3^3 xx x^(5/3 xx 3))` `=(12x^5)/(27 xx x^5)=4/9`

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes